Our iceberg is melting: managing organisational change - Anuar, Azyyati; Selvaraj, Bawani; Sadek, Daing Maruak (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
John Kotter and Holger Rathgeber’s Our Iceberg Is Melting: Changing and Succeeding Under Any Conditions (2006) is a sought-after, award-winning book on leadership. The eight principles mainly revolve around managing change, initiating change, getting others to change, and creating a new culture in an organisation/workplace. The penguin colony in Antarctica is used as an analogy to show the challenges faced by employers and employees in the real world. The story and characters in this fable are like people that we know and recognise, including ourselves. It evokes powerful emotions where most people fear change, which is often associated with confusion and resistance. Thus, this article sets out to review the eight-step process required for change in any organisation. The story Louis led a colony that had a Leadership Council known as the Group of Ten. Two hundred and sixty penguins lived in the colony, and among them was Fred, the curious and observant one, who fished less and researched more about the iceberg and sea. He gathered information (based on his observation) that the iceberg they are currently inhabiting could collapse, which would be disastrous for the penguins. He approached Alice, one of the ten leaders who had a reputation for getting things done, alerting her about this phenomenon. When Alice contacted all the members of the Leadership Council, they were very sceptical. Alice asked Louis to invite Fred to give a talk at the next Leadership Council meeting, and he agreed. Fred had discovered a huge hollow inside the iceberg filled with seawater. As winter approached, the water would freeze, expanding the ice and subsequently shattering the iceberg into pieces. Fred’s explanation was compelling – he constructed a model of the iceberg to show the hollow inside. Some of the other leaders resisted, saying Fred could not prove his theory, claiming that he was creating unwarranted anxiety and worry. Alice told Louis that the colony would hold him and all the leaders responsible if Fred was right.